Loan access, skill acquisition, bonding and the moderating effect of self-confidence on women entrepreneurs' business performance: A case of Nigeria - Isidore, Ekpe; Che Razak, Razli; Mat, Norsiah (The Social Sciences Research Society, 2012)
The objective of this study was to examine the moderating effect of self-confidence in business on the relationship between loan access, skill acquisition and bonding; and women entrepreneurs’ business performance. A quantitative research method (survey) was used to solicit responses from 161 women clients of three homogenous micro-finance institutions in Nigeria.The samples were selected through stratified proportionate random sampling. Data were analyzed using hierarchical regression. The results indicated that loan access (loan access), skill acquisition (skill acquisition) and bonding (bonding) had significant positive influence on women entrepreneurs' business (sales) performance in Nigeria.Self-confidence moderated the relationship between loan access and skill acquisition (not bonding); and women entrepreneurs' sales performance.